DETRITAL SEDIMENT FLUXES FROM CONTINENTS TO OCEANS - Hay W.W. (My University, 1998)
Detrital sediment is carried from land to the sea by three agents, rivers, glaciers, and winds. The shoreline is an arbitrary boundary within the detrital sediment transport system, which extends from a site of origin across areas of temporary storage to a site of long-term deposition. The most important of the agents moving sediment across the land is river transport, estimated to be in the order of 20#1012 kg of sediment annually at present. Analysis of drainage basins indicates that relief and runoff are the most important factors in determining the sediment load of rivers. The competence of rivers to transport sediment is governed by the volume flow, gradient, and the sediment load itself. Today, most large rivers are fed by snowmelt in highland areas, runoff from rainfall in the drainage basin, and groundwater inflow. Along the river course, water is lost to evaporation and groundwater infiltration. River courses can often be divided into two segments, a degradational section in which the gradient is relatively steep and little temporary storage of sediment takes place, and an aggradational section where the gradient is sharply reduced through meandering, and where large-scale temporary sediment storage forms a flood plain. Lakes trap sediment inland and prevent its transport to the sea. Today, many high and mid-latitude rivers are interrupted by lakes of glacial origin. There are also some large areas of internal drainage that deliver no sediment to the sea. The load carried by rivers has been markedly altered by human activity, and may have doubled over the past few thousand years, only to be reduced in the past century by the widespread construction of dams. The ancient use of fire in hunting and its subsequent use in clearing land has increased erosion. Extensive deforestation and cultivation processes have also increased the sediment supply. Dam construction is a relatively new factor and affects the sediment transport system by trapping sediment before it can reach the sea. The resulting lower sediment supply from rivers is, at least in part, compensated by increased coastal erosion. Glacial erosion is difficult to estimate. There is an ongoing controversy whether ice sheets are effective erosive agents or not. Estimates of the present global flux of glacial detritus range from 0.8-50#1012 kg annually, with the lower value most probable. The dust flux is in the order of 0.5 to 0.9#1012 kg annually, but may vary greatly with time.